Making grafting accessible to vegetable producers: An online multistakeholder economic decision-support system for vegetable grafting - Yefan Nian; Zhifeng Gao; Xin Zhao; Junhong Chen (Smart Agricultural Technology)
Vegetable grafting is a sustainable and eco-friendly practice for vegetable producers to manage plant diseases, boost plant nutrients and water absorption, and increase fruit yields and quality. To better promote the practice among U.S. vegetable producers and enhance the research and extension efforts regarding vegetable grafting, an online multistakeholder vegetable grafting economic decision support system (DSS) is developed. Users can rely on the DSS to conduct partial-budget, sensitivity, and breakeven analyses to comprehensively assess the economic implications of using vegetable grafting in various farm operations. The DSS also provides an essential platform for researchers, extension personnel, and producers to share information on the economics of vegetable grafting. It can serve as a valuable tool for stakeholders to analyze the economic feasibility of vegetable grafting and promote connections between various stakeholders, including producers, extension personnel, and researchers.